Academic-industry integration in health : enhancing postgraduate professional learning : final report. - Theobald, Karen; McCarthy, Alexandra; Henderson, Amanda; Coyer, Fiona; Shaban, Ramon; Fox, Robyn; Thomson, Bernadette (Australia. Dept of Education and Training (DET), 2019)
Nursing, paramedicine and allied health are significant players in clinical – academic settings, at the postgraduate level. Health systems depend on specialised disciplinary contribution and high - functioning, team - based approaches to patient care. In health contexts, the aim of postgraduate professional learning is to enable a clinically - educated and research - literate workforce to translate evidence into practice within regulatory frameworks and organisational expectations (Dzau et al., 2013). Billett's Australian Learning and Teaching Council Fellowship work emphasises that, when it is well - designed and delivered, work - integrated education contributes enormously to students' professional learning (Billett, 2007). Professional learning in this respect relies on the development of capabilities through teaching and learning experiences that integrate academic, discipline - specific and industry - referenced knowledge, skills and attitudes (Papadopoulos et al., 2011). Health services and faculties invest significant resources into their respective postgraduate curricula. These curricula range from practical to intensely theoretical, and from short professional development modules to Australian Qualifications Framework (AQF)-compliant units and programs. This current approach often results in duplication of both curricula and resource investment in the health and higher education sectors (Dzau et al., 2013). This project recognise d that, although industry and universities bring complementary knowledge and skills to curriculum development, each is driven by different organisational imperatives, resulting in divergent goals and approaches for curricula and different metrics to capture educational outputs (Dzau et al., 2013). In developing the shared culture of curriculum development advocated in this project, the universities and health services that deliver postgraduate education worked in a co - design partnership, striving for relevance, efficiency and agility to develop a mutually agreed framework for professional learning. [Executive summary, ed]